2017
DOI: 10.1002/jcb.25770
|View full text |Cite
|
Sign up to set email alerts
|

New Potential Biomarker Proteins for Alcoholic Liver Disease Identified by a Comparative Proteomics Approach

Abstract: Chronic alcohol consumption causes hepatic steatosis, which is characterized by a considerable increase in free fatty acid (FFA) and triglyceride levels. To identify the possible proteins involved in the progression to alcoholic hepatosteatosis, we performed proteomic analysis on livers of mice exposed to alcohol. 2D-based proteomic analysis revealed that EtOH exposure in mice changed the expression of 43 proteins compared with that in mice fed a normal diet (ND). The most notable protein changes were proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…100,101 Preclinical studies in mouse models of ALD applied proteomic (MALDI-TOF) analysis of livers and identified a cluster of differentially expressed proteins associated with ALD. 102 Interestingly, most of these proteins were also increased in NASH livers and only ornithine aminotransferase, vitamin D binding protein and phosphatidylethanolaminebinding protein were higher in ALD compared to NASH and normal controls. 102 In a mouse model of ALD, proteomic analysis of circulating extracellular vesicles (EVs) revealed a unique cluster or EVassociated proteins that were increased compared to control EVs.…”
Section: Key Pointmentioning
confidence: 91%
See 1 more Smart Citation
“…100,101 Preclinical studies in mouse models of ALD applied proteomic (MALDI-TOF) analysis of livers and identified a cluster of differentially expressed proteins associated with ALD. 102 Interestingly, most of these proteins were also increased in NASH livers and only ornithine aminotransferase, vitamin D binding protein and phosphatidylethanolaminebinding protein were higher in ALD compared to NASH and normal controls. 102 In a mouse model of ALD, proteomic analysis of circulating extracellular vesicles (EVs) revealed a unique cluster or EVassociated proteins that were increased compared to control EVs.…”
Section: Key Pointmentioning
confidence: 91%
“…102 Interestingly, most of these proteins were also increased in NASH livers and only ornithine aminotransferase, vitamin D binding protein and phosphatidylethanolaminebinding protein were higher in ALD compared to NASH and normal controls. 102 In a mouse model of ALD, proteomic analysis of circulating extracellular vesicles (EVs) revealed a unique cluster or EVassociated proteins that were increased compared to control EVs. 103 Among these was heat-shock protein-90 (hsp90) that was also associated with a biological effect in macrophages after exosome transfer both in vitro and in vivo, indicating both the biomarker potential of EV-associated proteins as well as the potential role of EVs in cell-to-cell communication.…”
Section: Key Pointmentioning
confidence: 91%
“…Oxidant stress plays a dominant role in the pathogenesis of ALD, as multiple studies have shown that generation of ROS is key for the progression of fatty liver to steatohepatitis and cirrhosis [23,24,25,26,27]. They induce pathological changes such as steatosis, inflammatory cell infiltration, hepatomegaly, fibrosis and cirrhosis [28].…”
Section: Key Players In Aldmentioning
confidence: 99%
“…The imbalance between de novo lipid synthesis and lipid β-oxidation accompanying alcohol consumption leads to the accumulation of lipid droplets in hepatic parenchyma [ 73 ]. Ethanol metabolism is also associated with up-regulation of sterol regulatory element binding protein 1c (SREBP-1c) and down-regulation of peroxisome proliferator activated receptor alpha (PPARα) [ 74 , 75 ]. Aberrated expression of the abovementioned receptors promotes fatty acid synthesis and simultaneously inhibits β-oxidation [ 76 , 77 ].…”
Section: Alcohol High Fat Diet and Mitochondriamentioning
confidence: 99%